Radiographic Progression-Free Survival as a Clinically Meaningful End Point in Metastatic Castration-Resistant Prostate Cancer: The PREVAIL Randomized Clinical Trial - Rathkopf, Dana E. (JAMA Oncol, 2018)
IMPORTANCE: Drug development for metastatic castration-resistant prostate cancer has been limited by a lack of clinically relevant trial end points short of overall survival (OS). Radiographic progression-free survival (rPFS) as defined by the Prostate Cancer Clinical Trials Working Group 2 (PCWG2) is a candidate end point that represents a clinically meaningful benefit to patients. OBJECTIVE: To demonstrate the robustness of the PCWG2 definition and to examine the relationship between rPFS and OS. DESIGN, SETTING, AND PARTICIPANTS: PREVAIL was a phase 3, randomized, double-blind, placebo-controlled multinational study that enrolled 1717 chemotherapy-naive men with metastatic castration-resistant prostate cancer from September 2010 through September 2012. The data were analyzed in November 2016. INTERVENTIONS: Patients were randomized 1:1 to enzalutamide 160 mg or placebo until confirmed radiographic disease progression or a skeletal-related event and initiation of either cytotoxic chemotherapy or an investigational agent for prostate cancer treatment. MAIN OUTCOMES AND MEASURES: Sensitivity analyses (SAs) of investigator-assessed rPFS were performed using the final rPFS data cutoff (May 6, 2012; 439 events; SA1) and the interim OS data cutoff (September 16, 2013; 540 events; SA2). Additional SAs using investigator-assessed rPFS from the final rPFS data cutoff assessed the impact of skeletal-related events (SA3), clinical progression (SA4), a confirmatory scan for soft-tissue disease progression (SA5), and all deaths regardless of time after study drug discontinuation (SA6). Correlations between investigator-assessed rPFS (SA2) and OS were calculated using Spearman ρ and Kendall τ via Clayton copula. RESULTS: In the 1717 men (mean age, 72.0 [range, 43.0-93.0] years in enzalutamide arm and 71.0 [range, 42.0-93.0] years in placebo arm), enzalutamide significantly reduced risk of radiographic progression or death in all SAs, with hazard ratios of 0.22 (SA1; 95% CI, 0.18-0.27), 0.31 (SA2; 95% CI, 0.27-0.35), 0.21 (SA3; 95% CI, 0.18-0.26), 0.21 (SA4; 95% CI, 0.17-0.26), 0.23 (SA5; 95% CI, 0.19-0.30), and 0.23 (SA6; 95% CI, 0.19-0.30) (P < .001 for all). Correlations of rPFS and OS in enzalutamide-treated patients were 0.89 (95% CI, 0.86-0.92) by Spearman ρ and 0.72 (95% CI, 0.68-0.77) by Kendall τ. CONCLUSIONS AND RELEVANCE: Sensitivity analyses in PREVAIL demonstrated the robustness of the PCWG2 rPFS definition using additional measures of progression. There was concordance between central and investigator review and a positive correlation between rPFS and OS among enzalutamide-treated patients. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT01212991